If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12(6+x)=8(5+x)
We move all terms to the left:
12(6+x)-(8(5+x))=0
We add all the numbers together, and all the variables
12(x+6)-(8(x+5))=0
We multiply parentheses
12x-(8(x+5))+72=0
We calculate terms in parentheses: -(8(x+5)), so:We get rid of parentheses
8(x+5)
We multiply parentheses
8x+40
Back to the equation:
-(8x+40)
12x-8x-40+72=0
We add all the numbers together, and all the variables
4x+32=0
We move all terms containing x to the left, all other terms to the right
4x=-32
x=-32/4
x=-8
| 39-5p=79-2P+80-8p | | 12(6+x)=8(x+12£ | | 8(x+9)=12(x-5) | | A+31=a+1 | | -134q+8;q=8 | | 4(x-5)=18- | | 1-3k=2-2k | | 10=7–6m | | 10=7–6m | | 3-y/3=-1 | | 10(x+5)=10(x+10) | | -2(x+7)=6(x-5) | | 10(x-5)=10(x+10) | | -6(5+2x)=3x-15 | | 22(z+8)=18(z+2) | | (3k+1)(7)= | | A^2–2a–35=0 | | a^2+64=607 | | x-3+8+4-3=16+8 | | 96=8(3+3k) | | -9(x-2)=-6x+27 | | 12y-6y+y-6y+2y=15 | | 9×700=x | | 6r=-28 | | -3x-48=-6(x+3) | | -3x-48=-6(x+3 | | 14v-13v=18 | | -135=3(-6b+3) | | 10n^2-11n-15=-18 | | 4x+5/7+3x=x/7-1/9 | | 6(x-3)=-9x-48 | | 20k-16k=12 |